Strategic Risk Management of Cardiovascular Diseases: An Analysis of Blood Pressure Control and Medication Adherence Based on the WHO/ISH Framework at Lolo Public Health Center - Franski Yuatama (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
Cardiovascular disease (CVD) is a systemic threat to global health and economic stability that requires a strategic risk management approach at the primary care level. This study aims to analyze the relationship between blood pressure control and medication adherence with the risk of cardiovascular disease in hypertensive patients at the Lolo Community Health Center, using the WHO/ISH Cardiovascular Risk Chart risk stratification instrument. This study used a quantitative observational design in a chronic patient population. From a health management perspective, weaknesses in the adherence monitoring system and inconsistent clinical control were determinants that increased the patient risk profile into the high and very high categories. Integration of Good Corporate Governance (GCG) principles, particularly the aspects of risk data transparency and service accountability, is crucial in mitigating the risk of treatment failure. The study results recommend reconstructing standard operating procedures (SOPs) at the Lolo Community Health Center by adopting a data-driven risk management model to sustainably reduce cardiovascular morbidity and mortality rates.